Construction of GFP gene into yeast vector - Farhana, Muhammad Yusoff (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The construction of Green Fluorescent Protein (GFP) gene into yeast vector is very important to ensure the successful of expression of GFP gene in yeast, Pichia pastoris. The GFP gene that was constructed into yeast vector, pPICZ A due to the easy to be manipulated genetically and culture than mammalian cells and can be grown to high cell densities compared to other expression system that available. The technique used in this study is mainly about amplifying the gene by using Polymerase Chain Reaction (PCR). The product was attempted to clone into pGEM-T and the transformation process was done by using heat shock method. Instead of using pGEM-T cloning method, the PCR product was subcloned directly into pPICZ A vector. The confirmation of positive transformant which contain of pPICZ A/ GFP was done to ensure the successful of construction of GFP gene into yeast vector by using colony PCR. This might be prior things in order to continue the next step in recombinant DNA technology.